Poems For Children - Kate James; James, Kate. (New York : Jellybean Press ; Avenel, N.J. : Distributed by Outlet Book Co., 1993)
A illustrated collection of poems, including Browning's "Pied Piper of Hamelin" and Lear's "The Owl and the Pussycat."
Includes index.
Keywords: Children's poetry, English; English poetry -- Collections; American poetry -- Collections